2022
DOI: 10.1073/pnas.2118283119
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a spatial repellent for control of Aedes -borne virus transmission: A cluster-randomized trial in Iquitos, Peru

Abstract: Over half the world’s population is at risk for viruses transmitted by Aedes mosquitoes, such as dengue and Zika. The primary vector, Aedes aegypti , thrives in urban environments. Despite decades of effort, cases and geographic range of Aedes -borne viruses (ABVs) continue to expand. Rigorously proven vector control interventions that measure protective efficacy against ABV diseases are limited to Wolbachia in a si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…This individual used the IM-app to determine and record the number of intervention units applied inside each house at initial deployment [based on manufacturer specifications of target density (one unit per 9 m 2 )] and record the timing of intervention deployment, replacement, or removal (Table 1 ). The SM-team included 35 nurse-technicians, each with a mobile device, who used the SM-app to record census updates from 4039 houses and outcomes from routine subject febrile illness surveillance to identify potential dengue or Zika virus infection [ 37 ]. Both the IM and SM teams were responsible for reporting indicators of potential adverse events in subjects and family members of enrolled houses.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…This individual used the IM-app to determine and record the number of intervention units applied inside each house at initial deployment [based on manufacturer specifications of target density (one unit per 9 m 2 )] and record the timing of intervention deployment, replacement, or removal (Table 1 ). The SM-team included 35 nurse-technicians, each with a mobile device, who used the SM-app to record census updates from 4039 houses and outcomes from routine subject febrile illness surveillance to identify potential dengue or Zika virus infection [ 37 ]. Both the IM and SM teams were responsible for reporting indicators of potential adverse events in subjects and family members of enrolled houses.…”
Section: Main Textmentioning
confidence: 99%
“…Here we describe the development, implementation and lessons learned from the use of a MDC system in a phase III randomized-cluster, placebo-controlled clinical trial evaluating the efficacy of a SR to reduce human infection with Aedes -borne viruses in the urban setting of Iquitos, Peru [ 20 ]. The overarching aim is to inform health stakeholders (investigators, funders, industries, health authorities) of the challenges and advantages of implementing MDC systems in similar field trials.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous SR trial, an effect size of 30% is conservative. [4] More informative for sample size calculations, the coefficient of variation in that trial was estimated following Hayes and Moulton to be 0.021. This was a low coefficient of variation, so for purposes of these sample size calculations, we assume the coefficient of variation is 0.15.…”
Section: Sample Size {14}mentioning
confidence: 99%
“…A recent study in Iquitos, Peru demonstrated a significant protective effect of a SR product against Aedesborne virus (ABV) transmission with a statistically significant reduction in the density of indoor female Aedes aegypti mosquitoes. [4] The use of a SR to demonstrate a reduction in ABV transmission has not been evaluated at large-scale in Asia. If effective, it could enhance vector control practices in the region and/or worldwide by complementing current disease prevention strategies.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%
See 1 more Smart Citation